2017
DOI: 10.1111/acel.12605
|View full text |Cite
|
Sign up to set email alerts
|

The space where aging acts: focus on the GABAergic synapse

Abstract: SummaryAs it was established that aging is not associated with massive neuronal loss, as was believed in the mid‐20th Century, scientific interest has addressed the influence of aging on particular neuronal subpopulations and their synaptic contacts, which constitute the substrate for neural plasticity. Inhibitory neurons represent the most complex and diverse group of neurons, showing distinct molecular and physiological characteristics and possessing a compelling ability to control the physiology of neural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 154 publications
(189 reference statements)
7
112
0
Order By: Relevance
“…The altered molecular pathways suggested by these transcriptomic findings include reduced neurotrophic support, neuronal signaling, and GABA function. These pathways have also been implicated in normal lifelong aging of the brain (21,22), lending support to the notion that depression may be associated with accelerated, or anticipated, molecular brain aging (21,23). Finally, functional neuroimaging studies suggest normal aging is associated with blunted CLC processing of emotional faces (24), mirroring neural activity patterns observed in specific depression subtypes (7)(8)(9)(10)12).…”
Section: Introductionmentioning
confidence: 78%
“…The altered molecular pathways suggested by these transcriptomic findings include reduced neurotrophic support, neuronal signaling, and GABA function. These pathways have also been implicated in normal lifelong aging of the brain (21,22), lending support to the notion that depression may be associated with accelerated, or anticipated, molecular brain aging (21,23). Finally, functional neuroimaging studies suggest normal aging is associated with blunted CLC processing of emotional faces (24), mirroring neural activity patterns observed in specific depression subtypes (7)(8)(9)(10)12).…”
Section: Introductionmentioning
confidence: 78%
“…An age‐related reduction in GABAergic input might contribute to attenuated photic entrainment (Benloucif, Masana, & Dubocovich, ; Zhang et al., ) and altered coordination of circadian oscillators during senescence (Davidson, Yamazaki, Arble, Menaker, & Block, ; Yamazaki et al., ). As well as the SCN, age‐related impairments in GABAergic systems have been identified in the cortex and other brain regions and have been implicated in cognitive impairments associated with aging and neurodegeneration (see Rozycka & Liguz‐Lecznar, for review).…”
Section: Neural Mechanisms Regulating Circadian Rhythms and How They mentioning
confidence: 99%
“…Vulnerability of inhibitory cortical interneurons towards aging 674Besides reduced excitability and plasticity(Clark & Taylor, 2011) and a decline of inhibitory 675 function(Cheng & Lin, 2013;Shetty & Turner, 1998;Stanley & Shetty, 2004), selective 676 vulnerability of particular neuronal subtypes, like inhibitory interneurons, and GABAergic synapses 677(Rozycka & Liguz-Lecznar, 2017) was reported for brain aging. Indeed, given the crucial role 678 GABAergic inhibitory interneurons have in cortical information processing, age-dependent defects in 679 inhibitory circuits provide an attractive hypothesis for the cognitive decline and age-associated 680 disorders(Rozycka & Liguz-Lecznar, 2017). 681In agreement with our finding that PV interneuron numbers were reduced in old cortices, several 682 studies reported declined cell numbers of cortical interneuron subtypes across different species and 683 brain regions (reviewed inZimmer-Bensch, 2019).…”
mentioning
confidence: 99%